Sling Exercise Can Drive Cortical Representation of the Transversus Abdominis and Multifidus Muscles in Patients With Chronic Low Back Pain - Li, Xin; Zhang, Haojie; Lo, Wai Leung Ambrose; Ge, Le; Miao, Ping; Liu, Howe; Li, Le; Wang, Chuhuai (Frontiers in Neurology, 2022)
Transversus abdominis (TrA) and multifidus (MF) muscles are essential in preventing chronic low back pain (CLBP) recurrence by maintaining segmental stabilization and stiffness. Sling exercise is a high-level core stability training to effectively improve the activities of the TrA and MF muscles. However, the neural mechanism for sling exercise-induced neural plasticity change in the primary motor cortex (M1) remains unclear. The aim of this study was to investigate the role of sling exercise in the reorganization of the motor cortical representation of TrA and MF muscles. Twenty patients with CLBP and 10 healthy individuals were recruited. For map volume, area, center of gravity (CoG) location (medial-lateral location and anterior-posterior location), and latency, two-way ANOVA was performed to compare the effects of groups (CLBP-pre, CLBP-post, and healthy group) and the two muscles (TrA and MF muscle). Visual analogue scale (VAS), Ostwetry Disability Index (ODI) and postural balance stability were assessed at baseline and the end of 2 weeks of sling exercise. Linear correlations between VAS or ODI and CoG locations were assessed by Pearson’s correlation test. Two weeks of sling exercise induced both anterior-medial(P＜0.001) and anterior-posterior (P=0.025) shifts of the MF muscle representation at the left motor cortex in patients with CLBP. Anterior-medial (P=0.009) shift of the TrA muscle representation at the right motor cortex was observed in patients with CLBP. The motor cortical representation of the two muscles in patients with CLBP after sling exercise (TrA: 2.88 ± 0.27cm lateral and 1.53 ± 0.47cm anterior of vertex; MF: 3.02 ± 0.48cm lateral and 1.62 ± 0.40cm anterior of vertex) closely resembled that observed in healthy individuals (TrA:2.83 ± 0.48cm lateral and 2.00 ± 0.43cm anterior of vertex; MF: 2.94 ± 0.43cm lateral and 1.77 ± 0.48cm anterior of vertex). VAS and ODI were reduced following sling exercise (VAS: P < 0.001; ODI: P < 0.001). The study provides evidence that sling training can drive plasticity changes in the motor system which correspond with the reduction in pain and disability levels in patients with CLBP. The study was registered on the Chinese Clinical Trial Registry (clinical trial registration number: ChiCTR2100045904, http://www.chictr.org.cn/showproj.aspx?proj=125819.)